2021
DOI: 10.1155/2021/8258778
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as Information Transmitter to Global Equity Markets: Evidence from CEEMDAN-Based Transfer Entropy Approach

Abstract: This study provides an analysis of chaotic information transmission from the COVID-19 pandemic to global equity markets in a novel denoised frequency domain entropy framework. The current length of the pandemic data offers the opportunity to examine its role in the asymmetric behaviour patterns of investors according to time horizons and the diversification potentials available to them. We employ the total daily global confirmed cases of COVID-19 and 27 equity indices from December 31, 2019, to April 18, 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 79 publications
8
53
0
Order By: Relevance
“…All G7 markets except Japan were found to be net transmitters of shocks in the mid-to-long-term periods. The findings suggest that the nature of spillovers across and within the BRIC and G7 markets is time-frequency-dependent, which is consistent with the HMH [ 23 25 ] the AMH [ 22 ], and the CMH [ 34 ]. This observation accentuates the conclusion of Mensi et al [ 60 ] who revealed that volatility spillovers among Islamic and BRICS equities were time-frequency-dependent.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…All G7 markets except Japan were found to be net transmitters of shocks in the mid-to-long-term periods. The findings suggest that the nature of spillovers across and within the BRIC and G7 markets is time-frequency-dependent, which is consistent with the HMH [ 23 25 ] the AMH [ 22 ], and the CMH [ 34 ]. This observation accentuates the conclusion of Mensi et al [ 60 ] who revealed that volatility spillovers among Islamic and BRICS equities were time-frequency-dependent.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, although information travels across markets as a consequence of investor queries, information flows become more intense during times of market stress. This situation exemplifies Owusu Junior, Frimpong et al’s [ 34 ] competitive market hypothesis (CMH), which states that the intensity of information flows and spillover between markets of the same and different asset classes is exacerbated in part by rational, albeit rather irrational, investors’ never-ending search for competing rewards and risks to meet portfolio goals.…”
Section: Literature Reviewmentioning
confidence: 72%
See 3 more Smart Citations